Transient Characteristics Analysis of He-Xe Cooled Space Reactor Coupled with Brayton Cycle Nuclear Power System - WU Yangmao1, 2, TANG Simiao1, 2, ZHU Longxiang1, 2, LIAN Qiang1, 2, ZHANG Luteng1, 2, MA Zaiyong1, 2, SUN Wan1, 2, PAN Liangming1, 2 (Yuanzineng kexue jishu)
Space nuclear power is crucial for future space missions, providing reliable energy for long-duration operations. Gas-cooled nuclear reactors, with high coolant outlet temperatures, are well-suited for integration with a closed Brayton cycle to achieve efficient megawatt-class power generation. A Megawatt-class Advanced Gas-cooled Nuclear System (MAGNUS) was developed featuring a high-temperature gas-cooled reactor coupled with a closed Brayton cycle in this study, establishing a comprehensive mathematical and physical model. The reactor model incorporates point reactor kinetics, reactivity feedback, coolant flow heat transfer, and thermal behavior of the fuel and structural materials. The Brayton cycle model includes key components such as the turbine-alternator-compressor (TAC), recuperator, and gas cooler. A robust numerical method was employed for solution, and a transient system analysis program was developed. The program’s steady-state and transient results were validated, followed by transient analyses of key accident scenarios, including positive reactivity insertion accidents and TAC shaft speed reduction events. For a positive reactivity insertion below 0.152 reactivity insertion occurs, the reactor stabilizes at 3.67 MWt (117% of core rated thermal power), while thermal-to-electric conversion efficiency improves from 32.1% to 34.4%. Early activation of protective measures reduces the required negative reactivity compensation while maintaining high efficiency. In contrast, delayed intervention requires stronger negative reactivity, leading to a decrease in core temperature and a reduction in thermal efficiency. During TAC shaft speed reduction, reactor heat output remains proportional to system load. Within a safe operating range, adjusting shaft speed effectively improves efficiency by minimizing temperature differential losses. However, speed regulation is self-stabilizing only down to 80% of rated shaft speed. If the speed drops further, safety measures must be implemented to prevent coolant flow reduction, excessive reactor heating, and potential fuel cladding failure.